Senescence-Associated Pro-inflammatory Cytokines and Tumor Cell Plasticity - Vernot, Jean Paul (Frontiers in Molecular Biosciences, 2020)
The well-recognized cell phenotypic heterogeneity in tumours is a great challenge for cancer treatment. Dynamic interconversion and movement within a spectrum of different cell phenotypes (cellular plasticity) with the acquisition of specific cell functions is a fascinating biological puzzle, that represent an additional difficulty for cancer treatment and novel therapies development. The understanding of the molecular mechanisms responsible for moving or stabilizing tumour cells within this spectrum of variable states constitutes a valuable tool to overcome these challenges. In particular, cell transitions between epithelial and mesenchymal phenotypes (EMT-MET) are of relevant significance, since it has been shown that they confer drug resistance, invasiveness and metastatic ability, due to the simultaneous acquisition of stem-like cell properties by tumour cells. Multiple drivers participate in these epithelial-mesenchymal transitions. In particular, cellular senescence and prolonged exposure to senescence-associated soluble factors have been shown to unveil cell plasticity and stem-like cell properties. Also, tumour cells that scape from senescence can acquire stem-like cell properties and aggressiveness. By modulating gradually the composition of their secretome and the time of exposure, senescent cells may have differential effect on cell plasticity, not only on tumour cells but also on surrounding cells present in the microenvironment. Interestingly, pro-inflammatory cytokines, that can reinforce senescence and inflammation, may provide a dynamic microenvironment milieu with changing signals in time having varied effects on cell transitions, plasticity, stemness and therefore heterogeneity. This will confer different epithelial/mesenchymal traits and stem-like cell properties, combinations of which could be responsible for different cellular functions during cancer progression (survival, migration, invasion, colonization or proliferation). Additionally, cooperative behaviour between cells with different phenotypes could also modulate their cellular physiology and add complexity to their plasticity. Here, we will discuss the role of senescence and senescence-associated pro-inflammatory cytokines on the induction of cellular plasticity, their effect role in establishing particular states within this spectrum of cell phenotypes and how this is accompanied by stem-like cell properties that, as the epithelial transitions, may also have a continuum of characteristics providing tumour cells with functional adaptability specifically useful in the different stages of carcinogenesis.